Experiência de parto de mulheres com gestação de alto risco e em programa de visitação domiciliar - Sousa, Maria Aparecida Gracélia (2020)
In the current obstetric context, much has been discussed about ways of being born, given how impactful and transforming this event is in the lives of women and their families, and in society. Despite many advances, perinatal care is still centered on the biomedical and technocratic model, characterized by the primacy of technology over human relations, with little interest and respect for the values of women and of the family. Such a reality gives women a subordinate role before the system, especially in situations of greater vulnerability, as in the case of gestating and giving birth in the condition of high gestational risk. The present study, qualitative, exploratory and descriptive, aimed to analyze the repercussion of a home visitation program, as a complementary action to high-risk prenatal care, on the positive childbirth experience of women. The World Health Organization's positive experience in childbirth was listed as a conceptual basis and Bardin's thematic analysis was the methodological reference. Data collection took place in a municipality in the interior of São Paulo, from January to September 2019, through home visits to high-risk pregnant women, followed by individual and open interviews. The study had seven participants. Two thematic categories were elaborated, namely: "The birth of childbirth", "The prenatal delivery and home visits". The results showed that receiving the visit was an effective complement in the prenatal period, which had an impact on the personal empowerment of women in order to cope with adverse pregnancy situations and facilitated their experience in childbirth in the face of a high-risk pregnancy.